Pengaruh Rasio Keuangan Terhadap Return Saham Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Ayu Mutiara; Suhaidar Suhaidar (Jurusan Akuntansi, Fakultas Ekonomi, Universitas Bangka Belitung, 2013)
Stock return is one of the factors that encourages an investor to invest the fund in capital market, especially stock investment. Investor can do fundamental analysis with financial ratios to predict how much return that will be reached. This research used some financial ratios such as NPM, ROA, DER, CFTA, CR, EPS, and PER. The changes of financial performance will affect stock price. The purpose of this research is to investigate the influence of financial ratios (NPM, ROA, DER, CFTA, CR, EPS, and PER) on stock return of manufacturing firms that are listed on Indonesia Stock Exchange. In this research, the sample of the firms was drawn using a purposive sampling with specific criteria. The sampling process gave out 35 manufacturing firms as the samples which were listing on Indonesia Stock Exchange in 2004-2008. The method in collecting data was documentation which mainly collected from Indonesia Stock Exchange (IDX) and Indonesian Capital Market Directory (ICMD) 2006-2008. The statistic method is multiple regression linear by using EViews 5.0. The result of this study indicates that all independent variables (NPM, ROA, DER, CFTA, CR, EPS, PER) simultaneously have significant effect on dependent variable (stock return). Partially NPM, DER, CFTA, PER, and EPS variables have positive and significant effects on the stock return. Current Ratio (CR) has significant effect, but negative on the stock return. Return on Asset (ROA) doesn’t have the effect on the stock return.